Analysis of interface pressure for double curves in idiopathic scoliosis patients / Noor Asliza Ahmad - Noor Asliza, Ahmad (2021)
Scoliosis is a sideway curvature of the spine more than 10 degrees. Scoliosis is grouped into age groups where the children under the age of three, the disease is called "infantile scoliosis" and the ‘‘juvenile scoliosis’’ happen to children at the aged 3-10 years. “Idiopathic scoliosis" usually occurs in adolescent aged 10-15 years or who have not yet reached puberty. Scoliotic condition will get worse as the patient starts aging. This disease can be controlled if it can be detected early. However, if left untreated, the condition of the spine will get worse and will cause various health problems in the future including death. To date, the main cause of the disease is still unknown. However, there are several treatments available to control the progression. The treatment of this disease is determined based on the degree of curvature of a patient. For curve angle between 10 to 25 degrees, the way of treatment is observation and appropriate exercises, while 20-45 degrees curve patients will be asked to use custommade body braces. These special body braces are usually made up of plastic and need to be worn for more than 20 hours a day.Body brace has been proven to be effective in stopping the curve progression and delay the surgery. Chêneau brace is one of body brace types. Chêneau brace has proven its effectiveness in treating patients with idiopathic scoliosis for years. However, no studies have been reported on the analysis of interface pressure in patients with double curve idiopathic scoliosis. This thesis focuses on measuring the interface pressure exerted by the Chêneau brace. A total of 72 (60 girls and 12 boys) patients aged 10 years and older participated in this study. Two sensors were placed on the inside of the brace wall so that it is in contact with patient’s body. The F-Socket Transducer (9811E) reading was used to assess the pressure on the right thoracolumbar and left thoracic curves between normal and maximum tension iv and the pressure variation of this interface with some basic daily activities. Each patient was asked to perform nine basic daily activities, and the interface pressure for each activity were recorded for normal and maximum tension. The results showed that the mean peak pressure produced in adolescent idiopathic scoliosis curve was higher for right thoracic curve than left thoracolumbar curve in all tasks. Pressure increased significantly at the maximum inspiration task (p <0.0001) for both indentation types for normal and maximum stresses. Patient were followed-up for six months and patients were asked to wear the brace in maximum tension at all times of possible. The levels of correction for thoracic and thoracolumbar indentations were 23.2% and 34.5%, respectively, after 6 months of brace use (23 hours per day). However, we could not find a large correlation between the mean peak pressure in the standing position and the degree of scoliosis correction for the two curves having values of r = 0.158, p = 0.356 and r = –0.024, p = 0.889.